Innovative models of cooperative of independent workers for decent work in Europe (National Administration Journal, 2022)
The socio-economic context is constantly challenging traditional employment relationships while new forms of employment are emerging, with acute risk of precarity for workers. In Europe, some non-standard workers find collective action as a valid alternative to the isolation and experiment solidarity and access to social security thanks to innovative cooperative models. The argument of the research is that the cooperative of independent workers is a viable opportunity to secure the working path of non-standard workers. The research focuses on a multiple case study approach involving three European cooperatives: the Italian Doc Servizi, the European Smart, and the Parisian Coopaname. The analysis of common and different practices among the cooperatives will show how cooperation can mitigate non-standard workers isolation and precariousness, how similar strategies are applied in different European countries, and how legal frameworks influence the operability of cooperative models.
Keywords: Worker cooperative; non-standard employment; cooperative of independent workers; decent work